Global liver disease burdens and research trends: Analysis from a Chinese perspective - Xiao, Jia; Wang, Fei; Wong, Nai-Kei; He, Jinhan; Zhang, Rui; Sun, Ruijuan; Xu, Yanying; Liu, Yingxia; Li, Wei; Koike, Kazuo; He, Weiling; You, Hong; et al. (Journal of hepatology, 2019)
Liver diseases affect millions of people worldwide. In most developed countries, the incidence of viral hepatitis is waning as a result of modern advances in disease prevention, diagnosis, and therapies. Expanded programmes for systematic immunisation against hepatitis B virus have also significantly brought down the number of new cases in many countries, including China. In contrast, with the improvement in living standards, the prevalence of metabolic liver diseases including non-alcoholic fatty liver disease and alcohol-related liver disease is set to rise, ultimately leading to more cases of end-stage liver diseases (liver failure, cirrhosis, and liver cancer). Over the past 30 years, visionary governments of major nations have provided strong incentives for basic/clinical research, vaccination programmes, and drug discovery and development in the field of hepatology. To get rid of her unflattering title as the “leader in liver diseases”, China has also made a serious effort to initiate nationwide preventive measures for liver diseases, global partnerships, and mentoring programmes for young hepatologists. Instrumental to such progress is the continuous support of the National Natural Science Foundation of China (NSFC), which has helped hepatology to thrive in virtually all research directions within the country. In this article, we seek to provide stimulating glimpses into the evolving liver disease epidemiology, institutional research profiles, funding landscape, and drug development trends in China, with an attempt to compare her status and achievements with those of the United States, European countries, and Japan.